A new species of Bidens (Asteraceae: Coreopsidae) from Baja California Sur, Mexico - León de la Luz, José Luis; Medel-Narváez, Alfonso (Instituto de Ecología, A.C., 2013)
A new taxon of Asteraceae, Bidens cabopulmensis, from the Cape Region of Baja California Sur, is described and illustrated. It occurs on coastal sand dunes. The novelty is not especially close to the other eight known species of Bidens from the geographical area and differs by its habitat, life form, and details of the heads. It shares some characteristics with the mainland species, B. cronquistii, B. hintonii, and B. triplinervia. A key to identify the nine known species of Bidens native in the Cape Region is provided.